2003
DOI: 10.1093/pcp/pcg126
|View full text |Cite
|
Sign up to set email alerts
|

Is the LIM-domain Protein HaWLIM1 Associated with Cortical Microtubules in Sunflower Protoplasts?

Abstract: Flowering plants express several LIM-domain proteins related to the animal cystein-rich proteins. The expression of sunflower LIM genes was followed by RT-PCR in cultured sunflower protoplasts. A transcript was detected only for HaWLIM1, but not for the other two genes HaPLIM1 and HaPLIM2. Polyclonal antibodies raised against either full length recombinant HaWLIM1 protein or peptides recognized a 27 kDa polypeptide on Western blots. Immunocytolocalization studies showed that HaWLIM1 is located in the cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
1
11
1
Order By: Relevance
“…1). A clear nuclear labelling and a dotted cytoplasmic pattern were observed (Fig.2a), in accordance with published data (Brière et al 2003). With anti-chicken spectrin antibodies a network of thin filaments could be seen (Fig.…”
Section: In Vivo Antibody Uptake In Protoplastssupporting
confidence: 91%
“…1). A clear nuclear labelling and a dotted cytoplasmic pattern were observed (Fig.2a), in accordance with published data (Brière et al 2003). With anti-chicken spectrin antibodies a network of thin filaments could be seen (Fig.…”
Section: In Vivo Antibody Uptake In Protoplastssupporting
confidence: 91%
“…In tobacco, LIM1 was found to be a transcriptional regulator that was able to activate the expression of a b-glucuronidase reporter gene expressed under the control of the prxC2 promoter, and overexpression of LIM1 led to upregulated expression of PAL-box genes PAL, 4CL, and CAD. In addition, sunflower LIM1 was shown to bind to microtubules and has a nuclear function in interphase cells (Brière et al, 2003). Recently, it was reported the Nt-WLIM2 has dual functions in actin bundling and transcriptional activation of the histone gene, and it shuttles to the nucleus in response to cytoskeletal remodeling (Moes et al, 2013).…”
Section: Lim-domain Proteins Have Been Identified In Various Plants Andmentioning
confidence: 99%
“…Tobacco WLIM1 (Nt-LIM1) was found to bind specifically to the Phe ammonia lyase (PAL)-box element and activate the expression of a b-glucuronidase gene placed under the control of the promoter of the horseradish peroxidase C2 (prxC2) gene (Kaothien et al, 2002) in the phenylpropanoid biosynthesis pathway (Kawaoka et al, 2000;Kawaoka and Ebinuma, 2001), and tobacco WLIM2 was shown to bind to the octameric ciselements (Oct) and activate the expression of the basal histone gene involved in cell proliferation and cell cycle progression (Moes et al, 2013). In addition, several plant LIM-domain proteins, including tobacco WLIM1 and WLIM2, sunflower WLIM1, and Arabidopsis LIMs, have cytoplasmic-nuclear localization, and tobacco WLIM2 was shown to shuttle to the nucleus upon cytoskeleton remodeling (Brière et al, 2003;Thomas et al, 2006;Papuga et al, 2010;Moes et al, 2013). Although these results provide important evidence for the subcellular distribution, cytoskeletal function, and transcription factor functions of some plant LIMs, our understanding of the physiological relevance of the plant LIM-domain proteins remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, direct evidence for an interaction between plant LIMs and the actin cytoskeleton is still missing, and the functions of plant LIM proteins remain unclear. Moreover, the situation is rather confusing since an interaction between the sunflower LIM protein WLIM1 and microtubules in sunflower protoplasts has been suggested (Briè re et al, 2003).…”
Section: Introductionmentioning
confidence: 99%